Incidence and predictors of early seizures in intracerebral haemorrhage and the effect of tranexamic acid. (June 2020) - Law, Zhe Kang; England, Timothy J; Mistri, Amit K; Woodhouse, Lisa J; Cala, Lesley; Dineen, Rob; Ozturk, Serefnur; Beridze, Maia; Collins, Ronan; Bath, Philip M; Sprigg, Nikola
Introduction: Seizures are common after intracerebral haemorrhage. Tranexamic acid increases the risk of seizures in non-intracerebral haemorrhage population but its effect on post-intracerebral haemorrhage seizures is unknown. We explored the risk factors and outcomes of seizures after intracerebral haemorrhage and if tranexamic acid increased the risk of seizures in the Tranexamic acid for IntraCerebral Haemorrhage-2 trial. Patients and methods: Seizures were reported prospectively up to day 90. Cox regression analyses were used to determine the predictors of seizures within 90 days and early seizures (≤7 days). We explored the effect of early seizures on day 90 outcomes. Results: Of 2325 patients recruited, 193 (8.3%) had seizures including 163 (84.5%) early seizures and 30 (15.5%) late seizures (>7 days). Younger age (adjusted hazard ratio (aHR) 0.98 per year increase, 95% confidence interval (CI) 0.97–0.99; p  = 0.008), lobar haematoma (aHR 5.84, 95%CI 3.58–9.52; p  < 0.001), higher National Institute of Health Stroke Scale (aHR 1.03, 95%CI 1.01–1.06; p  = 0.014) and previous stroke (aHR 1.66, 95%CI 1.11–2.47; p  = 0.013) were associated with early seizures. Tranexamic acid did not increase the risk of seizure within 90 days. Early seizures were associated with worse modified Rankin Scale (adjusted odds ratio (aOR) 1.79, 95%CI 1.12–2.86, p  = 0.015) and increased risk of death (aOR 3.26, 95%CI 1.98–5.39; p  < 0.001) at day 90. Discussion and conclusion: Lobar haematoma was the strongest independent predictor of early seizures after intracerebral haemorrhage. Tranexamic acid did not increase the risk of post-intracerebral haemorrhage seizures in the first 90 days. Early seizures resulted in worse functional outcome and increased risk of death.